APPLICATION OF THE HARDWARE-SOFTWARE COMPLEX "SALIVA" IN INTERNATIONAL DIGITAL INTEGRATION FOR THE DIAGNOSIS OF GASTROINTESTINAL DISEASES (INTERNATIONAL SCIENTIFIC-ELECTRONIC JOURNAL “PIONEERING STUDIES AND THEORIES”, 2025)
This article examines the application of the hardware-software complex "Saliva" in the context of international digital integration for the diagnosis of gastrointestinal diseases. The relevance of this research is driven by the increasing demand for effective and innovative diagnostic methods that can be integrated into the digital healthcare systems of various countries.The "Saliva" complex represents an advanced technology that enables precise analysis of the gastrointestinal tract's condition through non-invasive methods. The article provides a detailed description of the operating principles of the complex, its advantages over traditional diagnostic methods, and discusses the prospects for using "Saliva" within the framework of international cooperation in digital medicine.The study analyzes the effectiveness of the complex in various clinical scenarios and evaluates the potential benefits of its implementation on an international level. Special attention is given to issues of data standardization and compatibility, which are key aspects for the successful integration of "Saliva" into global medical networks